Le rôle de la distance dans l’organisation des pratiques et des paysages agricoles : l’exemple du fonctionnement des exploitations laitières dans l’arc atlantique - Maxime Marie (Unité Mixte de Recherche 8504 Géographie-cités, 2009)
In the areas with a dairy production and in a hedgerow landscape surrounding, farms appear as the elementary units of the structuration of rural spaces and landscape. The study of the logics of organization of the farmers’ practices thus appears as a pertinent grid to analyze the dynamics of the transformations of agricultural spaces and landscapes. For the dairy farms of the Western Atlantic Europe, the factors linked to the morphology of the fields play a dominating part (plots pulverization, acreage of the farm). From this angle, the analysis of the part played by the distance of the fields from the farm buildings itself as far as the organization of the farmers’ practices is concerned, takes on a central place. How can we take this distance into account and measure it too? The methods coming from the development of the Geographical Information Systems bring along, in this field, interesting advances. Making a grid based on distance criteria to read farmers’ practices highlights the diversity of land use organization of dairy farms in various agricultural and spatial contexts (Galicia, Normandy and England). This diversity then sends back to the dynamics of changes of agricultural systems relating to the land concentration (increase of the farms’ size, land consolidation), relating to the production system (specialization, intensification) and relating to the farms functioning (mechanization, automation, development of cooperative societies).